(untitled) (Ustozlar uchun, 2024)
Abstract: This article explores the significance and effectiveness of modern textbooks in foreign language teaching. It highlights their key features, such as interactivity, cultural content, and their ability to develop essential language skills. The article also discusses the advantages and limitations of popular textbooks, including Cambridge English Empower, Oxford Discover, and New Headway. Special attention is given to the challenges of adapting foreign textbooks to local contexts and the importance of integrating supplementary materials and technologies. The article provides practical recommendations for educators and methodologists to choose and effectively utilize textbooks while addressing students’ needs and local conditions.